Monastic silviculture legacies and current old-growthness of silver fir (Abies alba) forests in the northern Apennines (Italy) - Motta, Renzo; Garbarino, Matteo; Berretti, Roberta; Bono, Alessia; Curovic, Milic; Dukić, Vojislav; Nola, Paola (Frontiers in Forests and Global Change, 2023)
Species-rich mixed silver fir (Abies alba Mill.) forests dominated in the northern Apennines, but climate and, mainly, anthropogenic land use provoked a sharp silver fir decline approximately 5000 years bp. The conservation of the silver fir in this region was mainly due to the establishment of monastic orders that preserved and even planted silver fir for its spiritual and economic value. In 1993, the best silver fir stands were included in the Parco Nazionale delle Foreste Casentinesi (FCNP), Monte Falterona e Campigna, and have been submitted to low-intensive management or strict protection regardless of past land use and cultural history. In this study, we have (1) analyzed the current structure of three silver fir forests that have had different ownership histories and (2) compared the structure of the three Italian forests among them and with two old-growth forests from the Dinaric Alps as a reference of naturalness. The results show that the current structures of the three Italian forests are very different among them and are strictly related to past land use and, mainly, to monastic legacies. Even if the Italian forests have experienced decades of low-intensity management or strict protection, they are currently structurally very different from Dinaric old-growth forests. Developing an old-growth structure in these forests can be very slow and, in some ways, unpredictable. The results also highlight the importance of recognizing protected areas as cultural landscapes that host an important biocultural diversity. The current risk is that by applying almost exclusive biodiversity-centered management and setting difficult or impossible-to-achieve biodiversity goals, total diversity will decrease, and biocultural diversity, the greatest richness of most European parks, will be lost.